Penyelenggaraan Community Certification Authority Untuk Pengamanan Sumber Daya Internet Oleh Komunitas Untuk Kesiapan Asean Regional E-Commerce - Makarim, Edmon (Jurnal Hukum & Pembangunan, 2015)
Indonesia should immediately establish a public key infrastructure to facilitate the use of digital signatures by the public, in particular to facilitate the public service. This is to accommodate the growing practice of the network reliability (web of trust) and multi-identity. To embody Community CA Indonesia, necessary legal research tinged with shades of interdisciplinary. Train of thought that the background for this research topic selection is the gap between law and technology dynamics, especially in the implementation of electronic security systems. Generally arranged that each Trust Services Providers have the responsibility and legal obligations are adhered to the imposition of proof. Technically the term Community CA does not have a standardized definitions, but usually addressed to the implementation of the CA to the benefit of both communities is done by giving a certificate for free or paid and technically embrace web-trust application